2013
DOI: 10.5713/ajas.2012.12607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbohydrate Sources and Levels of Cotton Seed Meal in Concentrate on Feed Intake, Nutrient Digestibility, Rumen Fermentation and Microbial Protein Synthesis in Young Dairy Bulls

Abstract: The objective of this study was to investigate the effect of levels of cottonseed meal with various carbohydrate sources in concentrate on feed intake, nutrient digestibility, rumen fermentation and microbial protein synthesis in dairy bulls. Four, 6 months old dairy bulls were randomly assigned to receive four dietary treatments according to a 2×2 factorial arrangement in a 4×4 Latin square design. Factor A was carbohydrate source; cassava chip (CC) and cassava chip+rice bran in the ratio of 3:1 (CR3:1), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 49 publications
(60 reference statements)
2
27
0
Order By: Relevance
“…This result did not in line with the dry matter digestibility which increased with the use of complete rations containing soybean by-product and soybean pod or concentrate based ration. Previous study showed that there were positive correlations between dry matter intakes and digestibilities with total VFA concentrations (Wanapat et al, 2013). Molar concentrations of VFA such as acetate, propionate, valerate, ratio of acetate/propionate, and methane estimation were similar among treatments showing that the efficiency of nutrient convertion to VFA products was not changed.…”
Section: Discussionmentioning
confidence: 72%
“…This result did not in line with the dry matter digestibility which increased with the use of complete rations containing soybean by-product and soybean pod or concentrate based ration. Previous study showed that there were positive correlations between dry matter intakes and digestibilities with total VFA concentrations (Wanapat et al, 2013). Molar concentrations of VFA such as acetate, propionate, valerate, ratio of acetate/propionate, and methane estimation were similar among treatments showing that the efficiency of nutrient convertion to VFA products was not changed.…”
Section: Discussionmentioning
confidence: 72%
“…However, in addition to fiber, cotton crop also produce a great amount of seed biomass (Bellaloui et al, 2015a;Pettigrew & Dowd, 2014). The residual fraction of cottonseed after oil crushing, called defatted cottonseed meal (CSM), is mainly used as soil amendment and animal feed (Broderick et al, 2013;Li et al, 2012;Wanapat et al, 2013). Thus, value added utilization of CSM products as industrial and biobased raw materials would increase the profitability of cotton growers and processors.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of concentrate proportion in a forage based diet did not affect on CP apparent digestibility in goats (CantalapiedraHijar et al, 2009) and in dairy bulls (Wanapat et al, 2013). There is some controversy regarding to the CP digestiblity when portion of dietary forage is increased, which is likely due to the type of ingredients used in some experiments (Lu et al, 2005;Kiran and Mutsvangwa, 2007).…”
Section: Discussion Feed Intake and Apparent Digestibilitymentioning
confidence: 97%
“…Intraruminally introduction of NDF gave the highest ammonia concentration compared to those of starch and corn dextrose in dairy cows (Hristov et al, 2005). Wanapat et al (2013) …”
Section: Ruminal Fermentationmentioning
confidence: 95%
See 1 more Smart Citation